Mind over machine: The power of human intuition and expertise in the era of the computer - Dreyfus, Hubert L.; Dreyfus, Stuart E. (New York Free Press, 1986)
Defining the limits of computer technology, the authors make a compelling case that binary logic will always be inferior to human intuitive ability. A stunning reaffirmation of human intelligence.